Base Catalyzed Transesterification of Neem (Azadirachta indica) Seed Oil - Abdelrahman, Maha Abdelrahman Abdelmawla; M. M. Mohammed, Anas; A. A. Yassin, Atif (Gezira Journal of Engineering and Applied Sciences, 2021)
Base catalyzed transesterification was used to examine biodiesel synthesis for utilizing Neem ( Azadirachta indica ) seed oil. In addition, physicochemical analysis of the Neem seed oil and biodiesel produced were determined mainly by the American Oil Chemist Society (AOCS) and the American Society for Testing and Materials (ASTM). The experiments were carried out by one-step alkali based catalyzed transesterification method, using low (0.73%) free fatty acids (FFA). High biodiesel yield 92.8 % w/w with 99% total conversion was achieved. It was found that the biodiesel specifications such as; kinematic viscosity (5.43cSt), density (0.8877 g/cm 3 ) and Flash point (166˚C). These fulfil the requirements of ASTM and the committee of standardization in Europe standard specifications (EN). The results found were highly reliable and showed that the Neem seed oil is attractive as feedstock and has potential for biodiesel production. Therefore, the study recommended that the non-edible oils are economically useful for biodiesel production.